Water pollution and distribution of the black fly (Diptera: Simuliidae) in the Atlantic Forest, Brazil - Tatiana N Docile; Ronaldo Figueiró; Leonardo H Gil-Azevedo; Jorge L Nessimian (Revista de Biología Tropical, 2015)
Abstract:Black flies have medical importance because some species are vectors of the Onchocerciasis and Mansonelosis, nevertheless, their ecology and potential use as bioindicators is still poorly studied in the Neotropical Region. In Brazil, bioindicators use is strongly focused in a multimetrical ecological index approach; this way, we investigated the black fly spatial distribution, in relation to abiotic factors correlated to water quality, to provide baseline information for their utilization as standalone indicators of lotic systems integrity. We have tested the hypothesis that environmental changes related to urbanization, lead to decreased abundance and loss in the number of species of the black fly fauna. The sampling was conducted in 10 urban and 10 preserved streams during the dry season (August-September) of 2012, in the mountainous region of Teresópolis, State of Rio de Janeiro, Brazil. The streams were characterized for their environmental integrity conditions and physico-chemical properties of water. In each stream, five different rapid points were sampled in a section of 50 meters, 10 meters apart from each other. The black flies were sampled with a kick-net sampler on rocky substrates. The material was separated and the larvae were sorted in morphotypes, and later, the final instar specimens were dissected and identified with the help of taxonomical literature at species level. A total abundance of 488 larvae from nine species were collected, 5 (1.02 %) in extremely impacted streams, 470 (96.31 %) in intermediate streams and 13 (2.66 %) in preserved streams. The visual evaluation (HII) differed in rela&tion to the water physico-chemical evaluation, in which more variation in the characterization of the sampling sites was observed. In Canonical Correspondence Analysis Simulium subpallidum, S. inscrustatumand S. pertinaxwere significantly associated with intermediate values of most of the variables, and then to intermediate impacted sites. On the other hand, Lutzsimulium hirticosta, S. subnigrumand Simuliumsp. A were associated to low values of chemical variables, and then to more preserved sites. Most studies on the bioindicator potential of Simuliidae have suggested an approach to agricultural impacts, while our results, on the other hand, showed that Simuliidae species were present in streams with intermediate urban pollution impacts, but absent in heavily impacted sites. Thus, our data suggested that some species are associated to more pristine breeding sites, such as L. hirticostaand Simuliumsp. A, while others may be good bioindicators of moderately impacted streams, such as S. pertinax, S. subnigrumand S. subpallidum.